O desconforto térmico provocado pelos equipamentos de proteção individual (epi) utilizados na aplicação de agrotóxicos - Marcelo Motta Veiga; Ronaldo Almeida; Francisco Duarte (Universidade do Porto, 2016)
Human metabolism produces heat during labor activities. The human body works as a thermodynamic system maintaining a steady body temperature. The use of Personal Protective Equipment (PPE) jeopardizes the heat dissipation, making difficult to keep ain body temperature at a comfortable level. This study analyzed the interference of PPE in workers' thermal comfort. This study made measurements of heart rate and body temperature of workers using PPE during the process of spraying pesticides. This study also made subjective evaluations of thermal sensation of workers through a questionnaire. The results demonstrated: (i) the inadequacy of PPE projects because they indicated a negative impact on body thermoregulation process and (ii) the existence of significant individual differences between the monitored workers, which may be related to different operating modes. This study showed that there is a strong correlation between the subjective evaluation of the thermal sensation by workers and body temperature measured.